Analisis Pembiayaan Istishna dan Musyarakah Terhadap Laba Bank Rakyat Indonesia (Bri) Syariah - Alya Suci Faridhah Safitri; Wirman Wirman; Adhityo Dwi Nugraha (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the results of the analysis on the effect of istishna and musharaka on profits at Bank Rakyat Indonesia (BRI). In terms of doing business, there are several mindsets in our society, one of which is cooperation. Cooperation is carried out with other banks so that the bank can compete. The results of this cooperation will later be used to finance investment and also working capital in returning capital from the bank. This case study was conducted at Bank Rakyat Indonesia (BRI). This study uses a quantitative method which uses sources from literature studies and present the numeric data of analysis. The results of this analysis are musharaka which has a positif and have a significant effect on profits at BRI Bank. Meanwhile, the istishna have the same results which is positive and a significant effect on Bank Rakyat Indonesia's profit.